ANSIEDADE E DEPRESSÃO EM PACIENTES SUBMETIDOS À CIRURGIA DE REVASCULARIZAÇÃO DO MIOCÁRDIO. - LULA, Josimary Lima da Silva (2016)
Background: Coronary artery bypass grafting (CABG) is a procedure performed in patients with coronary artery disease (CAD). Perioperatively this type of surgery, patients the most diverse emotions and feelings are exposed, among them anxiety and depression. Objective: To evaluate emotional aspects of patients undergoing coronary artery bypass surgery. Methods: This was a cross-sectional study conducted in São Luís - MA with 41 adult patients undergoing CABG. Anxiety was assessed by the Beck Anxiety Inventory (BAI) and depression by Beck Depression Inventory (BDI). Results: There were more often male (60.98%), under 65 (53.66%), average of 64.04 ± 9.02 years, incomplete primary education (29.27%), family income between one and two minimum wages, body mass index (BMI) (<25) (43.90%) and patients with hypertension (78.05%). The anxiety in the preoperative period was present in 60.98%, increasing postoperative (75.61%) and maintained the same frequency as the pre ICU (60.98%) with statistically significant differences for sex (p=0.032) in the postoperative period. Depression showed frequency of 72.50%, 82.93% and 82.93%, respectively preoperatively, post and ICU, in which the income was significant postoperative (p = 0.022) and in the ICU (p = 0.011), BMI (p = 0.0047) and hypertension (p=0.041) before. Conclusion: These data demonstrated the need to incorporate new assistance strategies to worry about the psychosocial dimensions of patients, thereby providing early diagnosis and treatment of anxiety disorders and depression.